Relationship between NUDT21 mediated alternative polyadenylation process and tumor - Xiao, Shan; Gu, Huan; Deng, Li; Yang, Xiongtao; Qiao, Dan; Zhang, Xudong; Zhang, Tian; Yu, Tao (Frontiers in Oncology, 2023)
Alternative polyadenylation (APA) is a molecular process that generates diversity at the 3' end of RNA polymerase II transcripts from over 60% of human genes. APA and microRNA regulation are both mechanisms of post-transcriptional regulation of gene expression. As a key molecular mechanism, Alternative polyadenylation often results in mRNA isoforms with the same coding sequence but different lengths of 3' UTRs, while microRNAs regulate gene expression by binding to specific mRNA 3' UTRs. Nudix Hydrolase 21 (NUDT21) is a crucial mediator involved in alternative polyadenylation (APA). Different studies have reported a dual role of NUDT21 in cancer (both oncogenic and tumor suppressor). The present review focuses on the functions of APA, miRNA and their interaction and roles in development of different types of tumors.NUDT21 mediated 3' UTR-APA changes can be used to generate specific signatures that can be used as potential biomarkers in development and disease. Due to the emerging role of NUDT21 as a regulator of the aforementioned RNA processing events, modulation of NUDT21 levels may be a novel viable therapeutic approach.